The mediating roles of obesity indicators and serum albumin in the association of DEET exposure with depression and sleep disorders in adults: evidence from NHANES 2007-2016 - Huangxin Zhu; Ruyi Tao; Qingyun Yu; Miao Yu; Yue Zhou; Qingan Fu (BMC Public Health)
Abstract Background DEET (N, N-diethyl-m-toluamide) is a widely used insect repellent with potential neurotoxic effects. However, its impact on mental health in the general population remains unclear. This study investigates the association between DEET exposure and depression and sleep disorders, exploring the mediating roles of obesity indicators and serum albumin. Methods Data from the National Health and Nutrition Examination Survey (NHANES) 2007–2016 were analyzed. Urinary levels of 3-(diethylaminoformyl) benzoic acid (DCBA), a DEET metabolite, were used as an exposure marker. Depression was defined according to the scores of Patient Health questionnaire-9 (PHQ-9), and sleep disorders were diagnosed according to participants' self-reports. Multivariate logistic regression and restricted cubic spline analysis were employed to assess the associations of DCBA with depression and sleep disorders. Mediating analyses explored the roles of obesity indicators and serum albumin. Subgroup analysis further explored the differences among different populations. Results Higher DCBA levels were positively associated with depression and sleep disorders. Mediating analysis revealed that body mass index (BMI), waist circumference (WC), and serum albumin mediated 11.16%, 12.66%, and 7.04% of the association between DEET exposure and depression, respectively. Subgroup analysis identified increased susceptibility among women and individuals of other races. Sensitivity analysis enhanced the robustness of the results. Conclusion DEET exposure is associated with an increased risk of depression and sleep disorders, mediated by obesity and liver function indicators. These findings highlight the need for public health measures to reduce DEET exposure and further research into its mechanisms of action on mental health.